Immune checkpoints, their control by immunotherapy and ovarian cancer - Bose, Chinmoy K. (Contemporary Oncology/Współczesna Onkologia, 2017)
Immune checkpoints are new targets for manipulation of immunological control over malignant tumors. They provide an important means to manage especially recurrent and refractory cancers and those cancers where there is an unmet need such as recurrent melanoma, renal cell carcinoma and recurrent ovarian cancer. As a new development this subject is experiencing rapid progress and multiple avenues are opening up. However, there are many hurdles to overcome, requiring constant updating, especially for students of ovarian cancer, who are looking at it with much hope.